2020
DOI: 10.1186/s41938-020-00297-y
|View full text |Cite
|
Sign up to set email alerts
|

Biofumigation potential of Indian mustard (Brassica juncea) to manage Rhizoctonia solani

Abstract: In Egypt, Rhizoctonia solani is an economically important fungal pathogen on many crops such as common bean causing serious yield losses. Biofumigation with Indian mustard (Brassica juncea), as a potential alternative to the restricted fumigant methyl bromide, is gaining attention in sustainable vegetable production. In this study, laboratory and greenhouse experiments were conducted to evaluate the biofumigation effect of B. juncea, used as dry plants, seed meal, seed powder, methanol extract, and fresh plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We found the Brassicaceae significantly reduced the abundance of potential plant fungal pathogens. Brassicaceae, and more specifically mustards, have been deemed ideal for biologically suppressing plant pathogens such as plant parasitic nematodes and fungal pathogens due to their production of glucosinolates and isothiocyanates [114][115][116][117][118][119][120][121][122]. However, it has also been shown that isothiocyanates produced by Brassica kaber and Brassica nigra inhibit mycorrhizal fungi [123].…”
Section: Soil Health: Linking Microbial Communities Agroecosystem Services and Crop Traitsmentioning
confidence: 99%
“…We found the Brassicaceae significantly reduced the abundance of potential plant fungal pathogens. Brassicaceae, and more specifically mustards, have been deemed ideal for biologically suppressing plant pathogens such as plant parasitic nematodes and fungal pathogens due to their production of glucosinolates and isothiocyanates [114][115][116][117][118][119][120][121][122]. However, it has also been shown that isothiocyanates produced by Brassica kaber and Brassica nigra inhibit mycorrhizal fungi [123].…”
Section: Soil Health: Linking Microbial Communities Agroecosystem Services and Crop Traitsmentioning
confidence: 99%
“…In laboratory trials, it has been found that isothiocyante (ITC) and nitriles are effective at controlling bacteria, fungus, insects, and nematodes as well as bacteria (Delaquis and Mazza, 1995;Sarwar et al, 1998;Noble et al, 1999). Abdallah and Kandil (2020) conducted few experiments to examine the effect of Brassica juncea, as a biofumigant . The best result was found in defetted seed meal against Rhizoctonia solani.…”
Section: Mustard As a Bio Fumigantmentioning
confidence: 99%
“…A recent laboratory and greenhouse study was carried out in Egypt which involved use of biofumigation with Indian mustard (Brassica juncea) to control Rhizoctonia solani infection of the common bean. They used Brassica juncea as fresh and dry plants, methanol extract, or seed powder and meal [16].…”
Section: Biofumigation (Biological Soil Disinfection)mentioning
confidence: 99%